Carlos Fuentes or the Defiance of Time - Volpi, Jorge (Anales de Literatura Hispanoamericana, 2008)
According to this article, La Celestina and Don Quixote are the two columns which sustain Carlos Fuentes' monumental Terra Nostra. The novel goes far beyond mere entertainment or adaptation to the environment that allows it to survive; it becomes demanding and creates a verbal architecture which aims to offer an allencompassing idea of reality and fiction. This rereading of the Mexican's vast novel studies the way the first part reflects the Spanish imperial court and its artists: El Greco, Velázquez, Zurbarán, as well as imaginary characters such as Lazarillo de Tormes. The second part of the novel focuses on the new world. The third part is interpreted as the creation of a new order, which arises from the fusion of the two earlier worlds.
Keywords: Spanish Literature; Siglo de Oro; New World; Fusion